Chest-Related Imaging Investigations During Multiple Waves of COVID-19 Infection in Hong Kong - Ng, Kei Shing; Vardhanabhuti, Varut (Frontiers in Medicine, 2021)
Background: The COVID-19 pandemic has caused significant disruption to healthcare worldwide. In this study, we aim to quantify its impact of chest related radiological procedures over the different waves of local infection in Hong Kong across the territory’s public hospitals. Methods: This was an observational study enrolling patients between January 2017 and December 2020. Consecutive population-based chest radiographs, CT, US and interventional radiology (IR) procedures were obtained public hospitals across Hong Kong. Results: A significant reduction of 10.0% (p < 0.001) in the total number of chest radiographs was observed. Non-significant reduction of 2.5% (p = 0.0989), 39.1% (p = 0.2135) and 1.9% (p = 0.8446) was observed for Chest CT, Chest US, and Chest IR procedures, respectively in 2020 compared to the projected values. Conclusion: Although, it was anticipated that there would be a significant impact to health services caused by the pandemic, for chest-related investigations in Hong Kong, the impact was not as severe. Quantitative analysis could help with future planning and public health decision making.